137 Is a dedicated HFpEF clinic effective in managing patients with heart failure with preserved fraction (HFpEF)?. (4th June 2021) - Tran, Patrick; Long, Thomas; Smith, Jessica; Banerjee, Prithwish
Abstract : Background: HFpEF is often diagnosed in elderly patients coupled with comorbidities and degrees of frailty. Given the lack of evidence-based therapies, the common maxim is to 'optimize comorbidities with a holistic approach, ' Joint cardiology-geriatric HFpEF clinics have been recommended but are unlikely to be sustainable with current resource constraints. To improve outcome a dedicated HFpEF clinic led by HF specialists was therefore piloted to include specific interventions: diuretics, fluid restriction (<1.5L/day), heart rate control (<70/min for sinus and <80/min for atrial fibrillation (AF)), blood pressure (BP) control (<130/80 mmHg), cardioversion for AF, exercise recommendation and control of non-cardiovascular comorbidities (e.g. diabetes, COPD, obesity). Methods: A single-centre retrospective analysis of 202 HFpEF out-patients was performed over a 12-month period. Diagnosis of HFpEF was based on a local diagnostic algorithm similar to the HFA-PEFF score recommended by ESC. Electronic and paper records were reviewed, capturing comorbidities, clinic interventions and follow-up. We also performed a pilot analyses of hospitalization and mortality rates between patients managed in the general HF clinic and in the dedicated HFpEF clinic. Results: The study population reflected a typical HFpEF profile (mean age 79±9.6 years, 55% female, NYHA Class III/IV (48%), hypertension (78%), AF, 53%, chronic kidney disease (41%), ischaemic heart disease (30%) and obesity (13%) ( table 1 ). Clinic time was limited to 15-20 minutes. The majority of clinic interventions were cardiology-focused, namely congestion management (64%), drug reviews (86%) of anti-hypertensives, and rate/rhythm control of AF (48%). With the current outpatient structure, there was little remaining time to consider non-cardiac comorbidities. Although not powered in the pilot analysis, preliminary data showed no difference in hospitalization and mortality rates between general HF and dedicated HFpEF clinics. In both clinics, 25% of patients had at least two admissions at 12 months mainly due to non-cardiac causes ( table 2 ). Conclusion: Structure of specialized HFpEF clinics needs to be reshaped to meet the complex demands of HFpEF and improve patient outcomes. Current clinic activities concentrated on managing fluid balance, BP and cardiac drug reviews with little emphasis on comorbidities e.g. optimizing diabetes, anaemia or addressing polypharmacy which are common causes for re-hospitalization. We believe that our outpatient clinic reflects most HF clinics in the UK. Accordingly, an efficient HFpEF clinic pathway needs to be formulated. Quality improvement ideas include (1) screening patients before clinic for any significant comorbidities to enable early specialist advice or referral (2) entrusting HF nurse specialists to oversee current clinic activities allowing cardiologists more time for a holistic approach (3) adapting virtual clinics for regular follow-ups. Conflict of Interest: None